Analysis Vulnerability Website Baleomolcreative dengan Metode Penetration Testing Execution Standard & Vulnerability Assessment Pada Http Response Header Field - Kurniawan, Henokh; Christianto, Erwien (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research will analyze web security and how to find out whether there is a vulnerability or what could be called a vulnerability to enter gaps in the Baleomolcreative web, making the web unsafe. In analyzing whether there are vulnerabilities, the Penetration Testing Execution Standard and Vulnerability Assessment methods are used to determine whether there are gaps or vulnerabilities in the Baleomolcreative website that can be exploited by external parties. This method uses tools such as Owasp ZAP, Nikto, and Nmap which can be used to perform vulnerability scanning on a website. In this research, we succeeded in identifying 3 levels of vulnerability on the Baleomolcreative website, namely medium, low, and informational, with a total of 18 alerts generated from notifications on Owasp Zap. The scanning process includes vulnerability testing such as Content Security Policy, Anti-clickjacking Header, Dangerous JS Functions, Permissions Policy, and others.